Optimisation of insertion point during latissimus dorsi tendon transfer - Thompson, Seth Mkhanyisi (Division of Biomedical Engineering, 2019)
Problem and Motivation: Posterior rotator cuff injuries are common (Yamaguchi et al., 2006), (Neri et al., 2009) and often debilitating and irreparable (Sim et al., 2001). Latissimus dorsi (LD) tendon transfers have been shown to be an effective treatment for these massive or irreparable tears (Habermeyer, 2006), (De Casas et al., 2014). This procedure can have unpredictable outcomes (Ling et al., 2009). This is partially caused by discrepancies in the suggested insertion site for the LD tendon during transfers. The current literature is composed of in-silico studies which ignore the practicalities of the human body (Magermans et al., 2004), in-vivo studies which use subjective pain scores, and small scale cadaver trials. For these reasons, a study is needed that uses the power of in-silico modeling in a way that is verified using in-vitro testing on cadavers. Aims and Objectives: The aim of this study is to determine the effects of varying the insertion point of the LD tendon on the humeral head to treat posterior rotator cuff tears in terms of the effects on strength, primarily in rotation and in flexion over a range of motion. The objectives are to use an in-silico model to define the effects of various insertion points and validate this model using a cadaver trial before presenting the final findings. Methods: In-silico Model The Upper Extremity Model (Holzbaur et al., 2005) was used to simulate tendon transfers. The moment arms in flexion and rotation were measured and recorded at angles of 0° and 90° of forward ix elevation. The moment arms at each point were then projected onto humeral maps to display the results. Cadaver Trial Four fresh frozen cadaver torsos (eight shoulders) were mounted into a specifically designed rig. The LD was transferred to 7 points illustrative of the humeral head. The strain generated by the humerus in rotation on the clamps was measured at 0° and 90° of forward flexion for each point. These were then compared. Results In-silico Model The in-silico moment arm maps were generated and analysed. The optimal point for external rotation at 0° of flexion was the lesser tuberosity. Moment arms to produce external rotation were found over the entire greater tuberosity. Flexion was only generated on the posterior edge of the greater tuberosity. At 90° of flexion, little to no rotation generating moment arms were found in the lesser tuberosity and the anterior ridge of the greater tuberosity. Rotation generating moment arms were not significantly different between the posterior edge and the face of the greater tuberosity. No areas generated flexion moment arms. Cadaver Trial At 0° of flexion, the lesser tuberosity (point 1) generated the most flexion, with the greater tuberosity (points 2-7) also generating external rotation, but at reduced levels. At 90° of flexion, the lesser tuberosity and the anterior ridges of the greater tuberosty (points 1-3) generated no significant rotation. The posterior ridge and face of the greater tuberosity generated similar amounts of flexion, greater than points 1-3 Conclusions: The in-silico model was validated in rotation by the cadaver trials and this validation was extended to flexion. For maximum rotation strength at 0° of flexion and no flexion strength, the x lesser tuberosity is the optimal point. For maximum rotation strength and no flexion throughout the motion of flexion, the middle of the face of the greater tuberosity is the optimal area. For maximum rotation throughout the motion of flexion, points 4 and 5 (the posterior edge of the greater tuberosity) represent the optimal area for insertion. This area represents the optimal compromise in terms of range of motion and strength.